Characteristics of Asthma In Children at Prof. dr. I.G.N.G Ngoerah General Hospital - Putri, Novia Supoyo; Subanda, Ida Bagus; Windiani, I Gusti Ayu Trisna; Karyana, I Putu Gede (E-Jurnal Medika Udayana, 2025)
“CHARACTERISTICS OF ASTHMA IN CHILDREN AT PROF. DR. I.G.N.G NGOERAH GENERAL HOSPITAL” Background: Asthma is a chronic inflammatory disease of the respiratory tract which results in narrowing of the airways and is often found in children. Indonesia has a fairly high incidence of asthma in children when compared to adult asthma. Bali is ranked 6th with a fairly high prevalence of asthma in children aged 1-10 years. Asthma sufferers children in Bali tend to increase, but in RSUP itself there is no data on the number of asthma sufferers every year so it is necessary to do research at RSUP. Prof. dr. I.G.N.G Ngoerah General Hospital Objective: To find out the characteristics of children who suffer from asthma in RSUP. Prof. dr. I.G.N.G Ngoerah General Hospital 2020-2021. Methods: This research was conducted using a descriptive research method using a cross-sectional approach to determine the characteristics of children with asthma RSUP Prof. dr. I.G.N.G Ngoerah General Hospital 2020-2021. Results: Obtained children who suffer from asthma at Prof. Hospital. dr. I.G.N.G Ngoerah in 2020-2021 as many as 29 children with the highest cases found in children with male gender (62.1%), children aged 5-11 years (48.3%). In children with normal birth weight (79.3%), overweight (48.3%), and had a family history of atopy (20.7%) and exposure to cigarette smoke (13.8%). Conclusion: Based on the results of the research on the characteristics of children with asthma in RSUP. Prof. dr. I.G.N.G Ngoerah General Hospital 2020-2021 who met the research criteria, found that children with asthma were dominated by male children, in the age group 5-11 years, normal birth weight, overweight nutritional status, no family history of atopy and no exposure to cigarette smoke. Keywords: Asthma, characteristics, children